PENERAPAN METODE DEMONSTRASI PADA MATERI PENYAJIAN DATA TERHADAP HASIL BELAJAR SISWA DI KELAS IV SEKOLAH DASAR - Wira Lusiana; Bistari Bistari; Hery Kresnadi (Universitas Tanjungpura, 2021)
Abstract This study aimed to analyze the effect of the implementation of the demonstration method on data persentation material of student learning utcomes in class IV of 42 state elementari school, Pontianak City. The method used is the experimental method,the from of this research is a pre-expeimental design with a pretest-posttest group research design. The population is the entire fourth ggrade of 42 state elementary schools, Pontianak City district, which consist of 143 students. And sample is class IVA elementary school 42 students in Pontianak City, which consists of 26 students. Based on data analysis, the students average pre-test results were 57,5 and the students post-test average results were 70,5. The results of the t-test obtained tcount 3,13 while the t table white db =26-1=25 and the significant level (a)=5% is 1,706, it turn out that tcount > table or 3,13 > 1,706 then ha is accepted which means there is an effect of the application of the demontration method in the presentation of data on student learning outcomes in class IV of 42 state elementary schools, Pontianak City. This means that the application of the demonstration method has an effect of the student learningoutcomes in data presentation material in class IV of 42 state zElementary School, Pontianak District, City. Keywords: Influence, application, Demonstration Method, Learning Outcomes.